Implementation of Rudolf Bultmann's Demythologization Theory on the Stories in the Qur'an - Rakhman, Itmam Aulia (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This research is motivated by the presence of an interpretative gap in understanding Qur'anic stories containing supra-rational dimensions amidst the dominance of the modern-scientific paradigm. This study aims to critically adapt Rudolf Bultmann's theory of demythologization to extract the existential meaning (kerygma) from Qur'anic stories, while preserving the authenticity and sanctity of revelation. Through a qualitative content analysis approach that integrates Mohammed Arkoun's perspective, this research develops a methodological framework that filters the demythologization process through the principles of Ulūm al-Tafsir in the form of a hermeneutics of recovery. The research findings reveal three substantive points: first, the formulation of a hierarchical and systematic five-stage implementation model; second, the successful identification of the profound kerygma from three Qur'anic stories based on Angelika Neuwirth's two basic categorizations: Myths of Nature in the event of the splitting of the Red Sea (Q.S. al-Baqarah [2]:50) as divine liberation from oppression; and Myths of Heroic Figures such as the story of Ashāb as-Sabt (Q.S. al-Baqarah [2]:65, Q.S. al-A'rāf [7]:163-166), moral degradation as a consequence of wickedness, and spiritual ascent towards enlightenment in the story of the Prophet Muhammad's Isrā’ (Q.S. al-Isrā' [17]:1); third, the proven effectiveness of hermeneutics of recovery as a methodological filter that maintains the dialectic between text and context within the epistemological framework of tafsir. The study concludes that the filtered integration between Bultmann's demythologization and the framework of Ulūm al-Tafsir not only enables relevant contextual readings but also preserves the miraculous nature and authority of the revelatory text. The contribution of this research lies in the development of a contemporary tafsir model that bridges tradition and modernity, while paving the way for the development of a more dynamic and responsive Qur'anic interpretation methodology.